2015
DOI: 10.1016/j.ejvs.2015.01.018
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular Revascularization for Carotid Artery Occlusion in Patients with Takayasu Arteritis

Abstract: In patients with Takayasu arteritis, carotid artery recanalization via endovascular surgery combined with immunosuppressive therapy is effective and can be performed safely and repeatedly. The improvement in carotid artery blood flow supplying the central nervous system relieves symptoms of cerebral ischemia and is associated with an improved quality of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 23 publications
(19 reference statements)
0
23
0
Order By: Relevance
“…Open surgery is generally not recommended until the active stage of TA is controlled. 14,15 However, two studies reported that the rate of restenosis does not increase in patients with active stage TA if immunosuppressive treatment is administered. 16,17 In the present study, the 12 Ascending aorta e bilateral carotid e ABVe bypass.…”
Section: Discussionmentioning
confidence: 99%
“…Open surgery is generally not recommended until the active stage of TA is controlled. 14,15 However, two studies reported that the rate of restenosis does not increase in patients with active stage TA if immunosuppressive treatment is administered. 16,17 In the present study, the 12 Ascending aorta e bilateral carotid e ABVe bypass.…”
Section: Discussionmentioning
confidence: 99%
“…The treatment of patients with multiple aortic arch branch involvement, including their occlusion, has been widely described [7,8,[15][16][17][18][19][20][21][22][23][24][25]. In most cases of patients with the active inflammatory phase of TA, the immunosuppressive treatment alone may be effective in reducing the cerebral ischaemic Photo 1.…”
Section: Is Minimally Invasive Treatment Still Possible In Multiple Ementioning
confidence: 99%
“…Sometimes surgical treatment is needed [15,17,18]. Both methods -endovascular and surgical -are featured with good long-and short-term results, provided that the patients undergo proper treatment [7,8,17,18].…”
Section: Is Minimally Invasive Treatment Still Possible In Multiple Ementioning
confidence: 99%
See 2 more Smart Citations